MENINGKATKAN KEMAMPUAN MENGENAL 5 NAMA RASUL ULUL AZMI DAN SIFATNYA MELALUI PENDEKATAN BERNYANYI PADA ANAK TUNAGRAHITA RINGAN KELAS D VI/C (Classroom Action Research di SLB Perwari Padang) - Susteriani, Mega Iswari, Elsa Efrina (Universitas Negeri Padang, 2013)
This research originated from observation and interview research with sixth grade teacher, that there are 3 people in class VI students who have difficulty in mastering the subject matter of Religion, was saturated with religious material that is too much and just be taught by lecture so that students have difficulty in remembering material taught. Therefore the action through singing approach. This study aims to improve the process of learning about the Apostle Ulul Religion Azmi, so as to improve students' ability to recognize the apostle ulul azmi in class VI SLB Perwari Padang. The approach used in this study is a qualitative approach. Research data in the form of information about the process obtained from the observations, the results of tests of learning and discussion process. Source of data is the process through the implementation of religious learning in the students' approach to singing in class VI tunagrahita SLB Perwari Padang. Research subjects consisted of sixth grade students tunagrahita SLB Perwari Padang, which consists of 3 people, all male sex. Research procedures performed through 4 phases: 1) planning 2) implementation, 3) observations, 4) reflection. From the research done shows that the average ability of students to write down the name and the name of the apostle ulul azmi and nature in the first cycle with a percentage of 50% and the second cycle has reached 100%. The conclusion of this research is singing approach can improve the ability to know the apostle ulul azmi on student mental retardation.